Study on the mechanism of titanium improving the hot ductility of peritectic microalloyed steels in brittle zone III. (2nd November 2021) - Yang, Xiaogang; Xie, Lifang; Lai, Chaobin; Luo, Diqiang
ABSTRACT: In the current article, the influence of titanium on the hot ductility of peritectic-microalloyed steels, in the temperature range 600°C to 950°C, was investigated by tensile testing. The morphology of the fracture and the behaviour of precipitates, inclusions and microstructures near the fracture surface were observed and discussed. It was found that within the test temperature range, the reduction in area values of titanium-bearing steels were almost greater than 40%, which were much larger than those of titanium-free steels. This improvement was due to the formation of (Tix Nb1-x )(Cy N1-y ) precipitates and titanium-aluminium oxides with high titanium content that could act as the nucleation sites for dimples to promote the occurrence of ductile fracture. In addition, the austenite grain was refined and more uniform in size. The thickness together with the maintain temperature range of the ferrite films which distribute only along austenite grain boundaries were reduced.